IDENTIFY THE CAUSES AND SOLUTIONS OF HYDRAULIC DECK CRANE NO. 2 MALFUNCTION ON MV SHIPS. HABCO CARINA - Derma Watty Sihombing; Tri Kismantoro; Boedojo Wiwoho; M.Rizki Septyanto; Almanar Pasaribu (Meteor STIP Marunda, 2023)
A deck crane is an auxiliary machine on board a ship that is useful for assisting ship operations such as loading and unloading activities or raising and lowering goods that can only be lifted by a deck crane. The deck crane on the writer's ship uses a hydraulic system, which is a system that uses the potential and power of liquid substances. The purpose of this study is to identify the causes of damage to the deck crane and the maintenance that must be done on the deck crane. The research method used in this research is descriptive qualitative. From this research method, the data obtained will be analyzed so as to get an overview and the right solution to solve the problems that occur in this research. Based on the results of this study, the deck crane on the MV. Habco Carina was damaged due to damage to the hydraulic motor and the ineffectiveness of the Plan Maintenance System (PMS) or lack of maintenance on the deck crane. As a result, ship operational activities become hampered and disrupted. The most effective solution to this problem is to replace the hydraulic motor with a new one and improve deck crane maintenance. The most effective treatment is to check the oil level before each deck crane operates. It is hoped that this research can become a reference or reference as well as additional knowledge for readers and writers who experience the same problems as this research.